FN3 protein fragment containing two type III fibronectin domains from B. longum GT15 binds to human tumor necrosis factor alpha in vitro. (October 2020) - Dyakov, Ilya N.; Mavletova, Dilara A.; Chernyshova, Irina N.; Snegireva, Nadezda A.; Gavrilova, Marina V.; Bushkova, Kristina K.; Dyachkova, Marina S.; Alekseeva, Maria G.; Danilenko, Valery N.
Abstract: Most species of the genus Bifidobacterium contain the gene cluster PFNA, which is presumably involved in the species-specific communication between bacteria and their hosts. The gene cluster PFNA consists of five genes including fn3, which codes for a protein containing two fibronectin type III domains. Each fibronectin domain contains sites similar to cytokine-binding sites of human receptors. Based on this finding we assumed that this protein would bind specifically to human cytokines in vitro . We cloned a fragment of the fn3 gene (1503 bp; 501 aa) containing two fibronectin domains, from the strain B. longum subsp. longum GT15. After cloning the fragment into the expression vector pET16b and expressing it in E. coli, the protein product was purified to a homogenous state for further analysis. Using the immunoferment method, we tested the purified fragment's ability to bind the following human cytokines: IL-1β, IL-6, IL-10, TNFα. We developed a sandwich ELISA system to detect any specific interactions between the purified protein and any of the studied cytokines. We found that the purified protein fragment only binds to TNFα. Highlights: Gut microorganisms experience pressure from factors of the host's immune system. Gut bacteria are able to respond to the presence of cytokines in the growth medium. Bifidobacteria play a significant role in shaping and sustaining the immune system. Bifidobacterial protein binds specifically to human cytokines in vitro .